2012
DOI: 10.4103/1319-2442.100865
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of the phosphate binders nicotinic acid and sevelamer hydrochloride in hemodialysis patients

Abstract: Hyperphosphatemia is a significant risk factor for the development of ectopic calcification and coronary artery diseases in patients on hemodialysis (HD), and must be controlled with the use of phosphate binders. Studies comparing the effects of sevelamer and nicotinic acid, both similar non-calcium and non-aluminum phosphate binders, are not available. In this study, 40 patients on HD with a serum phosphorus level of more than 6 mg/dL were enrolled. After a two week washout period without phosphate binders, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
1
11
2
Order By: Relevance
“…This finding is partially in line with the findings of the study conducted by Ahmadi et al (13) in which they studied hemodialysis patients and found that sevelamer decreases triglycerides levels but does not affect their LDL-C, HDL-C, and total serum cholesterol. However, our finding regarding the patients' lipid profile was inconsistent with the findings of the studies conducted by Chertow et al (14), Shantouf et al (15) and Burke et al (16).…”
supporting
confidence: 91%
“…This finding is partially in line with the findings of the study conducted by Ahmadi et al (13) in which they studied hemodialysis patients and found that sevelamer decreases triglycerides levels but does not affect their LDL-C, HDL-C, and total serum cholesterol. However, our finding regarding the patients' lipid profile was inconsistent with the findings of the studies conducted by Chertow et al (14), Shantouf et al (15) and Burke et al (16).…”
supporting
confidence: 91%
“…The authors concluded that Sevelamer had greater serum phosphate lowering effect. However, this conclusion was erroneous, because the difference in phosphate reduction between the 2 groups over the treatment period was in fact not statistically significant (p=0.3) [15]. It is, however, of note that the phosphate reduction of 1.7 mg/dl (>0.5 mmol/L) achieved in the Niacin group over a 1 month period [15] is greater than that achieved in this study and Cheng et al's study [9].…”
Section: Discussioncontrasting
confidence: 69%
“…Furthermore, this reduction was achieved with the same total daily dose of Niacin as our study, once again suggesting that low dose therapy may be sufficient. Despite the low dose of Niacin, Ahmadi et al found that the incidence of significant side effects (mainly flushing) prompting study withdrawal was high (25%) [15]. Although not adequately powered to examine this phenomenon, the lower incidence of side effects prompting withdrawal (<10%) in this study, suggests that extended release Niacin may be better tolerated than the immediate release form used by Ahmadi et al [15] None of our patients had hepatotoxicity or GI side effects.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations